Level of Digitalization and Gross Domestic Product by Regions: Measurement and Dependencies - Kolev, Konstantin; Tsoklinova, Maya (Research Papers, 2025)
A number of studies have identified significant differences in the level of digital knowledge, skills and competences between regions in Bulgaria, as well as the country lagging behind the DESI index values compared to the average for the European Union (EU). In this regard, to stimulate the digital transition, the European Commission has allocated a budget of a total of 1.6 billion euros, which represents 26% of all funds under the Recovery and Resilience Plan of Bulgaria. The latter testifies to Europe's efforts to create conditions for the development of digital technologies in the economy and society and their contribution to economic development. The purpose of this paper is based on system of indicators and the application of factor analysis, to construct a digitalization index by region in Bulgaria as well as to verify the strength and direction of the relationship between the established level of digitalization and GDP by regions.
Keywords: Gross domestic product; Digitization; Factor analysis; Pearson coefficient; Regions